Efektivitas Alat Peraga Terjun Payung Warna Warni Sebagai Sumber Belajar Dasar Dasar Sains di Sekolah Dasar Negeri Jubung 03, Sukorambi, Jember - I Ketut Mahardika; Singgih Baktiarso; Fidia Alhikmah Putri; Qurrotul Aini; Hilda Nur Fadila; Diah Indri Lestari (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to increase students' interest in learning models related to basic science based on visual aids. In the field of education, teaching aids are used to stimulate the thoughts, feelings, attention, and interest of students in teaching and learning activities. Elementary school students, of course, really need a learning medium to support the process of learning abstract science that they did not know before. The role of these teaching aids is to help make the abstraction of knowledge more real. Researchers collect data simply by using a variety of data sources, such as primary data—information obtained directly from SD Negeri 3 Jubung students. b. Secondary data, namely data through literature in the form of books, journals, research, and previous opinions that have been proven true. The results of the research indicate that there are differences in the abilities of the students to understand one example of downward vertical motion in the daily lives of 24 students from SD Negeri Jubung 3 in the Jember Regency. The test results show that the average learning outcomes with the help of visual aids show results that are in the high category. The acquisition of student scores increased, as evidenced by the presence of explanatory materials using teaching aids. During the research, the understanding of students and students' involvement in explaining the concepts in teaching aids was very enthusiastic